A comparison of the neuroprotective efficacy of individual oxime (HI-6) and combinations of oximes (HI-6+trimedoxime, HI-6+K203) in soman-poisoned rats - Kassa, Jiri; Karasova, Jana Zdarova; Tesarova, Sandra (Drug and chemical toxicology, 2011)
The ability of two combinations of oximes (HI-6+trimedoxime, HI-6+K203) to reduce soman-induced acute neurotoxic signs and symptoms was compared with the neuroprotective efficacy of the oxime HI-6 alone, using a functional observational battery. Soman-induced neurotoxicity and the neuroprotective effects of HI-6 alone and HI-6 combined with trimedoxime or K203 in rats poisoned with soman at a sublethal dose (90 μg/kg intramuscularly, i.m.; 80% of LD₅₀ value) were monitored by the functional observational battery at 24 hours following soman administration. The results indicate that both tested oxime mixtures combined with atropine were able to allow soman-poisoned rats to survive 24 hours following soman challenge, while 4 nontreated soman-poisoned rats and 1 soman-poisoned rat treated with oxime HI-6 alone combined with atropine died within 24 hours following soman poisoning. While the oxime HI-6 alone combined with atropine treatment was able to eliminate a few soman-induced neurotoxic signs and symptoms, both oxime mixtures showed higher neuroprotective efficacy in soman-poisoned rats. Especially, the combination of HI-6 with trimedoxime was able to eliminate most soman-induced neurotoxic signs and symptoms and markedly reduce acute neurotoxicity of soman in rats. Thus, both tested mixtures of oximes combined with atropine were able to increase the neuroprotective effectiveness of antidotal treatment of acute soman poisonings, compared to the individual oxime.
Keywords: Animals; potkani Wistar; neurotoxické syndromy; Rats, Wistar; Neurotoxicity Syndromes; oximy; Pyridinium Compounds; Molecular Structure; pohybová aktivita; pyridinové sloučeniny; chování zvířat; trimedoxim; molekulární struktura; Oximes; Male; Trimedoxime; Neuroprotective Agents; Soman; kombinovaná farmakoterapie; soman; krysa rodu Rattus; Behavior, Animal; Motor Activity; mužské pohlaví; zvířata; Rats; Drug Therapy, Combination; neuroprotektivní látky